2015
DOI: 10.1103/physreve.91.013011
|View full text |Cite
|
Sign up to set email alerts
|

Periodic emission of droplets from an oscillating electrified meniscus of a low-viscosity, highly conductive liquid

Abstract: The generation of identical droplets of controllable size in the micrometer range is a problem of much interest owing to the numerous technological applications of such droplets. This work reports an investigation of the regime of periodic emission of droplets from an electrified oscillating meniscus of a liquid of low viscosity and high electrical conductivity attached to the end of a capillary tube, which may be used to produce droplets more than ten times smaller than the diameter of the tube. To attain thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…When B E ≈ 1, the surface charge density approaches the Rayleigh limit, and the meniscus becomes electrically unstable, leading to the formation of conical tips, similar to those observed in microdripping in air. The emission is aperiodic at low q i and periodic at higher q i , similarly to what is observed in air …”
Section: Electro‐coflowsupporting
confidence: 76%
See 1 more Smart Citation
“…When B E ≈ 1, the surface charge density approaches the Rayleigh limit, and the meniscus becomes electrically unstable, leading to the formation of conical tips, similar to those observed in microdripping in air. The emission is aperiodic at low q i and periodic at higher q i , similarly to what is observed in air …”
Section: Electro‐coflowsupporting
confidence: 76%
“…The emission is aperiodic at low q i and periodic at higher q i , similarly to what is observed in air. [127,133,134]…”
Section: Microdrippingmentioning
confidence: 99%
“…The images and the pressure signal were synchronized through a data logger system. Each registered image of the forming bubble was digitally analyzed using an in-house twostep interface detection routine, similar to that described by Hijano et al (2015). Firstly, a rough detection of the edges of the needle tip and of the forming bubble is performed at the pixel level.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These suspensions can have high viscosity and high density due to high particle concentration 21,22 . Hijano et al 23 found that in an electrospray of low viscosity fluid, the process depends on two non-dimensional parameters: normalized flow rate and electric Bond number which is a measure of the square of the voltage. The current paper deals with the inception of a viscous droplet in the dripping regime as well as the microdripping regime.…”
Section: Multiple Modes Of Atomization In Electrosprays Are Affected mentioning
confidence: 99%